Diazotization Grafting Phenol for Improving the Electrochemical Performance of Graphite Anode. Issue 10 (1st October 2022) - Yang, Haohua; Lu, Yanmin; Li, Zhan; Wu, Xuena; Liu, Libin; Ban, Qing; Gai, Ligang
Abstract : Capacity fading resulting from graphite exfoliation is a thorny problem for real application of the graphite anodes in lithium-ion batteries. In this paper, we report on diazotization grafting phenol for graphite flakes to settle this issue, using 4-aminophenol and tert-butyl nitrite as the diazonium reagents. Diazotization grafting phenol enables expansion of graphite interlayer spacing and formation of surface protective layer, yielding modified graphite anodes with improved electrode kinetics, and significantly improved cycling stability. Also, the phenol modifier contributes additional specific capacity to the anode through reversible redox reaction of phenol hydroxyls with Li + ions. The modified graphite anode with mole percent of 4-aminophenol to graphite being 5% retains a discharge specific capacity of 361 mA h g ‒1 after 300 cycles at 1C, presenting capacity retention of 90.5% relative to the initial cycle, much higher than that of 156 mA h g ‒1 and 54.2% for pristine graphite.